NILAI-NILAI KARAKTER DI SEKOLAH DASAR NEGERI 127 PALEMBANG - Muttia Ratna (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This research was conducted qualitatively-descriptive which aims to describe the religious and discipline character of the students of grade 1 in Elementary School 127 Palembang. The data were collected using observation, questionnaire, and documentation. Data were analyzed using data reduction, data display, conclusion, and data verification. At this data reduction stage, the researcher used data triangulation from data observation, questionnaire, and documentation which is then displayed in the data view. From triangulation it was found that the religious and discipline character of the first grade students in SDN 127 Palembang has emerged as much as 80%. Thus it is concluded that students in class 1 SDN 127 Palembang has had the character of religious and discipline